Metoda Web Komputasi Untuk Perhitungan Intensitas Bencana Kekeringan Di Wilayah Indonesia - Plato Martuani Siregar; The Houw Liong; Bayong Tj H.K (Institut Teknologi Bandung, 2002)
Meteorological computation needs networking of database in synoptic analysis,that computated by single computer is wided to networking because it’s needed information for data processing that simultaneously,past,and accurately for weather prediction. Computation by internet is applied in CGI Language and database manajement by MySQL. All of atmospheric dynamics equation is implemented by CGI (php or perl programming). Computations of drought intensity use rain factor or drought index that develoved by climate elements,i.e,temperatures and rain fall. Value of drought index is less than 5.0 for drought condition,which rain fall in mm and temperature in Kelvin. El Niño event causes drought in Eastern and Southern of Indonesian region than non-El Niño year. El Niño gives drought for Indonesian region,but not all of drought caused by El Niño event,those are other factor for instantce east monsoon.